FAKTOR YANG MENJADI PREFERENSI KONSUMEN DALAM MEMBELI PRODUK FROZEN FOOD - Christopher Richie Rahardjo (Jurnal Performa)
Consumer's preferences towards products will continue to change over time. Therefore, it is important for a company to keep themselves updated with these preferences in order to develop their business. The objectives of this study are to determine: 1) the factors behind consumer's preferences in selecting frozen food products in west Surabaya; 2) the influence of these factors on consumer preferences in selecting frozen food products; and 3) the implementation of consumer preference factor on Indotaste's products. This research is a qualitative research with survey and interview as data collection methods. Surveys are conducted towards 40 consumers of frozen food, while the interviews are performed systematically to four consumers of Fiesta or So Good who have made repeat purchases and two consumers of Indotaste who have made at least three repeat purchases. Research results indicate that the most influential factor in consumer's preferences in choosing a frozen food product is taste, followed by price, packaging, and brand.